DETECTION OF GENETIC VARIATION OF IGF1R GENE POLYMORPHISM AND ITS RELATIONSHIP WITH ECONOMIC TRAITS OF GOAT. - Shlaka , Ali J.; Al-Khazraji , Wasan J.; Abdullah , Ali N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The field component of this study was conducted at the Ruminant Research Station affiliated with the Agricultural Research Department, Ministry of Agriculture, using a sample of 79 goats (32 Shami and 47 local). The laboratory phase was carried out at the Biotechnology Laboratory of the College of Agricultural Engineering Sciences, University of Baghdad, and the Advanced Scientific Laboratory for Genetic and Molecular Gene Technologies, with the aim of extracting genomic DNA. The experiment spanned from November 1, 2023, to May 1, 2024.The study focused on the IGF1R gene, specifically examining exon 12, intron 12, and exon 13, covering a 910-base-pair region. Results revealed two single nucleotide polymorphisms (SNPs) in the analyzed region: G267514A and G267782A. Analysis of the G267514A mutation in local goats identified three genotypes: wild-type (GG) at 71.1%, heterozygous (GA) at 26.67%, and mutant (AA) at 2.22%, with allele frequencies of 84% for G and 16% for A. In Shami goats, this mutation exhibited only two genotypes: wild-type (GG) at 93.75% and heterozygous (GA) at 6.25%, with allele frequencies of 97% for G and 3% for A.The study highlighted significant genetic variation between Shami and local goats regarding the G267514A mutation. This mutation influenced body dimensions, fertility rate, and milk production season length in local goats, while showing negligible effects in Shami goats. The G267782A mutation, however, showed no association with any production traits in either breed..